AUDIT ENERGI SISTEM PENCAHAYAAN DAN SISTEM TATA UDARA PADA GEDUNG ADMIN PLTU TANJUNG JATI B UNIT 3 & 4 - Saharul Alim; Zaenal Arifin; Muhammad Alif Najih; Aji Wicaksono (Jurnal Disprotek, 2021)
This study will analyze the suitability of the lighting and air conditioning systems installed with the provisions of SNI-6197-2011 and SNI-6390-2011, the value of energy consumption intensity in all buildings will be calculated and analyzed according to the regulation of the minister of energy and mineral resources 13 of 2012, and estimate possible opportunities. The results show that the value of energy consumption intensity is included in the very wasteful criteria, namely 50.38 kW/m2, so it is necessary to increase the energy audit, the most energy saving that is most likely to be done is high costs by replacing lighting equipment and air conditioning systems, for lighting systems by changing the type of lighting. 36W 36W TL lamps, 14.7W LED tube lamps and 18W PL lamps become 10W LED bulb lamps, while for the air conditioning system by replacing non-inverter coolers into inverter coolers and adjusting the cooling capacity according to the BTU/h needs of each room, thus saving electrical energy which is obtained is 138,399.49 kWh per month or if converted into Rp. 164,762,338.54 and the intensity of energy consumption is reduced to 13.66 kWh/m2 which is classified as quite efficient.